College transition Fall 2020 and 2021: Understanding the relationship of COVID-19 experiences and psychosocial correlates with anxiety and depression. - Andrea Lourie; Susan Kennedy; Erin J Henshaw; Drexler James (PLoS ONE, 2023)
Rates of mental health symptoms, particularly anxiety and depression, have increased significantly in college students in the past decade along with utilization of mental health resources. The COVID-19 pandemic created an additional source of stressors to an already challenging landscape of college transition. COVID-19 has been associated with an increase of anxiety among college students, particularly first year students, entering college in Fall 2020. The shifts in policy (e.g., federal, state, and college) accruing medical data, and vaccine availability between Fall 2020 and Fall 2021 provide an opportunity to examine the role of COVID-19 experiences in the transition to college for these two first-year student cohorts. This study examined two cohorts of first-year students, Fall 2020 and 2021, to better understand the relationship between COVID-19 experiences, psychosocial correlates, and mental health symptoms. Results suggest that for students in our Fall 2020 cohort COVID-19 experiences played a distinct role in the prediction of mental health symptoms while in Fall 2021 COVID-19 experiences did not uniquely contribute to prediction of mental health symptoms. These findings have implications for mental health interventions for first-year students transitioning to college.